Developing an Auditing Interactive Electronic Textbook With Google Slide and Quizizz - Nasrullah Djamil (STAI Hubbulwathan Duri, 2022)
This research was carried out at an undergraduate Accounting Department in a university at Pekanbaru, Riau. The participants were three auditing experts, an information technology expert, eight lecturers teaching auditing, and 87 students from the auditing department (they took Auditing 1, auditing 2, and auditing practice courses). This study adopted the R D method to develop an Interactive Electronic Textbook (BAEI) for Auditing courses using Google Slides and Quizizz applications. The results revealed that the auditing BAEI was designed to be validated by experts, a lecturers group, and students indicating a high interest in the developed auditing BAEI.